(Re)Generating Inclusive Cities : Poverty and Planning in Urban North America - Zuberi, Dan; Taylor, Ariel Judith (Abingdon, Oxon ; New York : Routledge, 2018)
"As suburban expansion declines, cities have become essential economic, cultural and social hubs of global connectivity. This book is about urban revitalization across North America, in cities including San Francisco, Toronto, Boston, Vancouver, New York and Seattle. Infrastructure projects including the High Line and Big Dig are explored alongside urban neighborhood creation and regeneration projects such as Hunters Point in San Francisco and Regent Park in Toronto. Today, these urban regeneration projects have evolved in the context of unprecedented neoliberal public policy and soaring real estate prices. Consequently, they make a complex contribution to urban inequality and poverty trends in many of these cities, including the suburbanization of immigrant settlement and rising inequality. (Re)Generating Inclusive Cities wrestles with challenging but important questions of urban planning, including who benefits and who loses with these urban regeneration schemes, and what policy tools can be used to mitigate harm? We propose a new way forward for understanding and promoting better urban design practices in order to build more socially just and inclusive cities and to ultimately improve the quality of urban life for all."--Provided by publisher.
chapter Introduction: Urban Renewal in North America in a Neoliberal Context -- chapter 1 Mega- projects From the Big Dig to the High Line: Regenerating the City -- chapter 2 Urban Renewal in North America Today: From HOPE VI to New Models of Inclusive Urban Redevelopment -- chapter 3 Creating New Urban Neighborhoods: The Post- industrial Transformation From Brownfield to Vibrant Community? -- chapter 4 Urban Renewal in Vancouver, Canada -- chapter 5 Urban Regeneration in North America Today: Outcomes, Trends and Future Challenges -- chapter 6 Conclusion and Recommendations.
Includes bibliographical references.
Keywords: Urban renewal; City planning